Instructional Design Principles in the Development of an E-Learning Graduate Course - Phillips, John Arul; Ansary Ahmed; Kaur , Kuldip (2005)
The paper reports the application of the science of instruction in the design and development of an e-Learning graduate course at Open University Malaysia (OUM) for the Masters of Education programme. Focus is on the principles applied to print material (content, learning outcomes, learning activities and assessment tasks) and its use in engineering face-to-face interaction, online collaboration, enhancing higher order thinking, utilisation of resources from the digital library, digital content bank, video and audio lectures. The learning and instructional theories underlying the design process of the graduate course are explicated.